Borrowing on the wrong credit card: Evidence from Mexico - Alejandro Ponce; Enrique Seira; Guillermo Zamarripa (Banco de México, 2014)
We study how consumers allocate debt across credit cards they already hold using new data on credit card activity for a representative sample of consumers with two homogeneous cards in Mexico. We find that relative prices are a very weak predictor of the allocation of debt, purchases, and payments. On average, consumers pay 31% above their minimum financing cost. Evidence on cross-card debt elasticities with respect to interest rates and credit limits show no substitution in the price margin. Our findings offer evidence against the cost-minimizing hypothesis and provide support to behavioral explanations.
Keywords: D12; D14; D40; G02; G20; G28; 330; credit cards; household finance; consumer behavior; Mexico